Kajian Perkembangan Pariwisata Kabupaten Cilacap sebagai Kawasan Strategis Pariwisata Provinsi Jawa Tengah - Zahra Ratu Aziza; Imam Buchori (Jurusan Perencanaan Wilayah dan Kota, 2020)
This research is based on the declining tourism development phenomenon in Cilacap Regency as much as 34% in 2017-2018. This indicates that the development of tourism is hampered, and has not been able to support the role of the Central Java Provincial Tourism Strategic Area (Kawasan Strategis Pariwisata Provinsi Jawa Tengah/KSPP) as a tourism policy for Cilacap Regency. Research found that lack of tourism attractions, tourism supply resources that tend not to be ready, are the main factors that inhibit the development of tourism in Cilacap Regency. These factors lead to imbalance tourism demand condition, such as declining tourists’ enthusiasm, lack of tourist arrivals outside Central Java Province, and there are no foreign tourists. The inhibit condition of combination in supply and demand tourism make the policy doesn’t suitable with the existing tourism development condition. Therefore, it is important to examine the causes of underdeveloped tourism in Cilacap Regency, so that it will be useful to make initial steps for developing Cilacap Regency in tourism sector